Robustly coordinated operation of a ship microgird with hybrid propulsion systems and hydrogen fuel cells. (15th April 2022) - Fan, Feilong; Aditya, Venkataraman; Xu, Yan; Cheong, Benjamin; Gupta, Amit K.
Graphical abstract: Highlights: A coordinated operation strategy considering the pre-voyage and intra-voyage optimization is proposed to minimize the operation cost of a ship microgrid. A comprehensive degradation model considering the increase of the ohmic area specific resistance and the drop of terminal voltage is developed to accurately calculate the degradation costs of FCs. A two-stage robust optimization approach is proposed to robustly optimize the operation of the ship microgrid. A two-level column-and-constraint-generation (C&CG) algorithm is used to solve the optimization model. Abstract: Increasing global greenhouse gas (GHG) emissions call for new operation strategies towards low-carbon marine transportation. This paper proposes a coordinated operation strategy for a ship micorgird with hybrid propulsion systems (HPSs) to minimize the whole-voyage operation cost within GHG emission limitations. Hydrogen fuel cells are integrated to the ship microgrid for further reduction of GHG emissions. Purchase costs of fuel, hydrogen and electricity and degradation costs of fuel cells (FCs) and batteries are considered in the calculation of whole-voyage operation cost. The proposed coordinated operation strategy consists of two stages. At the pre-voyage scheduling stage, the amount of purchased fuel, hydrogen and electricity, the power of diesel engines (DEs) and FCs, the charging/discharging states of batteries and the motor/shaft-generator modes of electric machines (EMs) are formulated to minimize the whole-voyage operation cost under the worst case of uncertain propulsion and auxiliary power. At the intra-voyage operation stage, power of batteries and EMs is optimized according to the short-leading-time prediction of propulsion and auxiliary power. Above coordinated operation strategy is formulated as a two-stage robust optimization model and solved by a two-level column-and-constraint-generation (C&CG) algorithm. Numerical simulations based on a practical voyage are carried out to validate the effectiveness of proposed strategy.